FAKTOR – FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Murni Indaharini, 14.05.52.0087; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
The purpose of this research is to analyze the influence of Auditor’s Opinion, Public Accountant Size, Financial Distress, Change in Management, Company Size, and Company’s Growth toward the Auditor Switching. This research was conducted at a manufacturing company listed on Indonesia Stock Exchange.In this study, the type of data used is secondary data. The sample is determined using purposive sampling in observation periode 2014 – 2016 the number of samples obtained as much as 267. The analyrical tool used was logistic regression method with SPSS 21 program. The results showed that Financial Distress and Company size significantly positive on the auditor switching. While auditor’s opinion, public acoountant size, change in manajemen, and company’s growth do not significantly affect the auditor switching Keywords : Auditor Switching, Auditor’s Opinion, Public Accountant Size, Financial Distress, Change in Management, Company Size, and Company’s Growth.